Development and Characterization of Edible Films from Sodium Alginate and Arrowroot Starch Plasticized with Sorbitol - Huynh, Tien Dat; Ngo, Pham Thao Nguyen; Nguyen, Vinh Tien; Wibowo, Condro (Universitas Jenderal Soedirman, 2025)
ABSTRACT. The demand for eco-friendly packaging is growing in industrial applications. This study aimed to develop edible films using sorbitol, sodium alginate (SA), and arrowroot starch (ARS). Sorbitol, serving as a plasticizer, was evaluated for optimal concentration, while various SA:ARS ratios were tested for film formation. Physicochemical properties, including thickness, color, tensile strength, elongation, moisture content, opacity, water solubility, water vapor transmission rate, biodegradability, FTIR, and SEM morphology were analyzed. Results indicated that 0.5% sorbitol produced films with ideal thickness, color, tensile strength, and elongation. SA:ARS ratios significantly influenced film properties, with the 0.9:0.1 ratio yielding a thin, smooth, and highly biodegradable film. This formulation provides a basis for further edible film research and food industry applications. Keywords: Arrowroot starch, edible film, sodium alginate, sorbitol